Recent advances in film dosimetry for quality assurance in microbeam radiation therapy - Sarvenaz Keshmiri; Gaëtan Lemaire; Adélie André; Florian Thevenet; Alexandre Ocadiz; Nicolas Rosuel; Benjamin Huffschmidt; Yacine Bencheikh; Mostafa Ghafooryan-Sangchooli; Paolo Pellicioli; Raphaël Serduc; Jean-François Adam (Scientific Reports)
Abstract Microbeam Radiation Therapy (MRT) is currently on the verge of entering the clinical phase, necessitating robust quality assurance (QA) with appropriate dosimeters to ensure patient safety. However, MRT dosimetry presents significant challenges due to its intrinsic characteristics, including steep dose gradients with alternating high and low dose regions—referred to as peaks and valleys (valley doses comprising only 5–7 $$%$$ of peak doses)—micrometric resolution requirements, the use of low-to-medium energy X-rays and extremely high dose rates of up to 16 kGy/s. Currently, Gafchromic films are considered the gold standard for patient QA. Previous studies have reported discrepancies of 10–30 $$%$$ between measured and calculated peak and valley doses. This study aimed to evaluate four types of films (EBT-3, EBT-XD, MD-V3, and HD-V2) to determine the most suitable option for MRT QA. To support dosimetric benchmarking, the microDiamond detector was used as the reference for MRT measurements, and the ionization chamber for broad beam reference dosimetry. Discrepancies were observed between calculated and film-measured peak and valley doses, and several hypotheses were proposed to explain these differences. Possible causes include simplifications in dose calculation engines, intrinsic limitations of the films, uncertainties in experimental setups, and variations in readout methods. The study suggests that MD-V3 may be the most suitable film for MRT dosimetry, offering a dynamic range that effectively covers both peak and valley doses.